Water Problems between Turkey, Bulgaria and Greece 1954-2015 Mareej River as a Model - Hameedy, Ismael Noori (Journal of Tikrit University for Humanities, 2020)
Turkey has many water problems with its neighbors in general, and with Bulgaria and Greece in particular, including the problem of the Mareej River, which has become one of the reasons why Turkey has not joined the European Union.The Mareej River, as much as it is a blessing for Bulgaria (being a source country), is a curse for Turkey and Greece (being two estuary countries), and it is considered a common factor between the three countries, and it is an international river in the eyes of Turkey, while in the eyes of Bulgaria it is not international. However, the problems of the river exist till now without any solutions from the three conflicting countries. Because of the intellectual, religious and political disparities of the three countries, the negative effects and tensions between the three countries remained.Turkey has started its serious interest in relation to the Mareeij River since its industrial and agricultural development has increased and its urgent need for its water in 1954, and differences occurred between the three countries over the sharing of water quotas, the construction of dams and the treatment of flood problems, and they have not yet been resolved despite the intervention of the European Union and the continuation of negotiations and numerous meetings. There are not any final solutions, and the reason is Bulgaria’s failure to comply with the decisions on international rivers.Turkey, because it is an estranged and non-member state of the European Union, is the weakest link, and the Turks always try to pursue a flexible policy with Bulgaria and Greece, and to exercise diplomatic and technical policy to find solutions to the problems of the river, as long as it needs its water and its problems continue to increase; The differences will not reach the level of war, and the method of holding the stick in the middle will remain the dominant one, and negotiations will continue.Key words: Bulgaria, Greece, Mareej River, Transboundary waters, Turkey, water policy of Turkey.